Fit and Feasibility: Adapting a Standardized Curriculum to Prepare Future Health Professionals to Address Alcohol Misuse. (June 2019) - King, Diane K.; Neander, Lucía L.; Edwards, Alexandra E.; Barnett, Jodi D.; Zold, Amanda L.; Hanson, Bridget L.
Standardized screening, brief intervention, and referral to treatment (SBIRT) is effective when used by health care professionals to assess, educate, and intervene to address risky alcohol use. To accelerate SBIRT training within academic settings, the Substance Abuse and Mental Health Services Administration funded implementation of its SBIRT curriculum to promote its use by future health care professionals. We report on how SBIRT content was implemented within nursing, social work, psychology, and family medicine residency programs at a state university. The reach, effectiveness, adoption, implementation, and maintenance (RE-AIM) evaluation framework was used to compare delivery of SBIRT curriculum across health professions. Survey data measured changes in student knowledge, confidence, and responsibility to use SBIRT for alcohol and drugs, pre- and post-SBIRT training. Twelve months postgraduation follow-up surveys examined maintenance of outcomes and SBIRT use in practice. Observational data explored fidelity and adaptations made to curriculum content and delivery logistics. Results indicated that instructor adoption, fidelity, and format varied across health professional training programs, with adaptations made to improve fit, role alignment, and cultural relevance. Despite variation in curriculum delivery, students demonstrated significant gains in knowledge and confidence, ( p < .001). Key implementation and maintenance challenges included time constraints, instructor buy-in, competing accreditation requirements, and costs for using the university simulation laboratory to practice SBIRT. Strengths supporting maintenance included flexibility to adapt curriculum, department champions, and electronic resources to support curriculum delivery. Results suggest that adaptations maximizing the feasibility and fit of SBIRT within existing courses enhanced its adoption and maintenance potential without sacrificing effectiveness.